Kontrowersje wokół pełnomocników przedsiębiorstw państwowych - Moskwa, Leopold (Wydział Prawa i Administracji UAM, 1985)
The present article attempts at settling a question concerning sources of a legal status of attorney (agent) in the enterprise, character of a legal relation linking the enterprise with its employee in the situation when the latter performs external acts, forms of appointing an attorney and admissibility of appointing fully empowered attorneys in the enterprise. The sole sources of power of attorney in the enterprise are: declaration of will of a director and the statute (art. 97, 464 and 734 par. 2 of the Civil Code). Interpretation of art. 45 sec. 1 of The State Enterprise Act brings to the conclusion that the director is vested not only with a competence of granting power of attorney but also of selecting the attorney's person. The enterprise's employee is not authorised to perform external acts on a base of the director's mandate addressed to him within the scope of defined "internal" relation. The said employee can act only on a base of civil law power of attorney. Granting a power of attorney requires only an ordinary written form for its validity. Art. 45 sec. 2 of The State Enterprise Act is the special provision in relation to the Civil Code provisions which are voicing the principle of freedom of form (art. 73 et seq.) and to art. 99 par. 1 and 2 c.c. On the grounds of art. 45 sec. 3 of The State Enterprise Act I assume the admissibility of granteeng all the three types of power of attorney by the state enterprise. In particular it is permissible for the director to grant a general power of attorney.
Controversies on attorneys of State enterprises